The Correlation The Internet Addiction Toward Teenagers Religiosity and Intelligence Quotient In Banjarmasin City - Imadduddin imadduddin; Yulia Hairina (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
The internet has become a primary need for everyone nowasdays, including teenagers. Ease access to information through the internet is one of factors that make teenagers addicted to the internet. The self-control factor is an important factor that is often associated with internet addiction, besides that internet addiction is also thought to be caused by a lack of internalization of religious values ​​or what is called religiosity and Intelligence Quotient. The research method in this study was field research by using descriptive and correlational quantitative approaches. The research subjects in this study were teenagers 14 to 24 years who lived in Banjarmasin city with totaling 712. The composition was 324 males and 388 females. The sampling technique used in this study was the Proportionate Stratified Random Sampling procedure, namely the sample selection process, where all members of the population had the same opportunity to be selected by considering the strata (levels). Based on the results of the study, it was found that the Sig-value was 0.972 (P>0.05). So, It could be concluded that internet addiction had no significant correlation to teenagers’ religiosity and Intelligence Quotient in Banjarmasin City.